Combination of occlusal splints and light therapy in temporomandibular disorder: Kombinasi splin oklusal dan terapi lampu pada temporomandibular disorder - Paulina, Tiroi; Syafrinani; Chairunnisa, Ricca (Makassar Dental Journal PDGI Makassar, 2024)
The most common temporomandibular disorder (TMD) is disc displacement with reduction (DDWR). Clicking as a characteristic symptom of DDWR requires conservative treatment such as occlusal splint. However, other accompanying symptoms such as pain in the masticatory muscles require additional treatment like physiotherapy. This paper aims to describe DDWR treatment using a stabilization splint and physiotherapy using infrared lamp therapy. A 33-year-old male came to the Prosthodontics Clinic with chief complaints that there is soreness on right jaw when he wakes up in the morning and was aware of it since a year ago. The patient has a habit of teeth grinding during sleep. Clinical examination, a sound on the right and left jaw joint when opening and closing the mouth, mouth opening without pain of 50.5 mm with deviation to the right, pain in the muscles around the face, especially the masseter, temporalis and trapezius. Radiograph shows the position of the right and left mandibular condyles an-terior to the articular tubercle. A stabilizing splint is used for symptomatic treatment and physiotherapy is carried out in the form of infrared lamp therapy. It is concluded that the combination of stabilizing splint and infrared lamp therapy can reduce pain and clicking in TMD’s patients.